ARSHIP : Autonomous Search Ship Untuk Mencari Korban Kecelakaan Hilang di Perairan - Agus Sutiyana; Akhmad Ikhsannul Arief; Firgi Aditya; Rahmat Hidayat (Sultan Publisher, 2025)
Unmanned Surface Vehicle (USV) is an unmanned surface vessel that can operate automatically or manually that can be controlled by humans. Unmanned Surface Vehicle (USV) is equipped with an autonomous navigation system. In addition, ARSHIP's electrical power supply is supplied with batteries integrated with solar panels so that battery power can be charged directly through solar power. This type of ship is used for search and rescue operations in water areas such as seas, rivers and lakes and as a support tool for the SAR team to carry out the evacuation process. This ship will detect the presence of victims in the waters by monitoring using YOLO as a human object detection. Based on the results of human object detection underwater using the YOLO model that has been customized with an average detection of 0.7 out of 1. The simulation results show that the model is good enough to predict human objects in the water.